Editorial - Journal, Editor UDSM Library (University of Dar es Salaam Library Journal, 2019)
This issue contains a variety of articles concerned with library and information science. The areas covered include: ICT usage in libraries, marketing and use of library resources, plagiarism information collaboration, information literacy and electronic resources. While most of the articles relate to experiences in Tanzania two focus on Nigeria.